PRISM: A decision support system for forest planning. (November 2022) - Nguyen, Dung; Henderson, Eric; Wei, Yu
Abstract: PRISM, a new forest management decision support system, was developed for United States national forest planning at the same time existing tools were deprecated. PRISM has a friendly graphical user interface to facilitate model development, database management, sensitivity analysis, and data visualization. It integrates SQLITE engine for database storage and exploration. It supports both classic forest planning Model I and II to schedule management activities and achieve multiple management objectives through the lifecycle of a forest plan. Multiple models may be created through the PRISM interface and solved in batch mode for convenient sensitivity analysis. Various options to visualize model outputs are available through the embedded JFREECHART library. The open-source nature of PRISM makes it free to use and allows for long-term software development and collaboration. This paper presents the architecture, core functionality, and selected applications of PRISM in the United States national forest planning. Highlights: PRISM is an open-source user-friendly decision support system for forest planning. PRISM schedules forest management activities to achieve long-term desired conditions with a goal programming approach. PRISM supports model development, database management, data visualization, and sensitivity analysis. Multiple national forests in the United States Northern Region have used PRISM to support land management planning.